Desempenho de novilhas de corte em pastejo suplementadas com concentrados - Silva Filho, Amorésio Souza (2015)
This study aimed to evaluate the effects of concentrate supplementation on performance of grazing beef heifers in the rainy season. The experiment was conducted in a rural property in the city of Rondonópolis-MT, located in the geographical coordinates Latitude 16°28’S, Longitude 54°38’W. The experimental period was from December of 2013 to May of 2014, lasting 136 days. The treatments were consisted of concentrated supplementation at the level of 0; 0.5 and 1.0% of body weight (BW) of the animals, being distributed in a randomized blocks with two repetitions (area). Each of the six experimental areas was composed of eight paddocks of 0.1 hectares and an area of 200 m2 with free access to the animals, in which the feeders and water drinkers were allocated. The grazing method adopted was the rotational stocking with variable stocking rate. It was used 36 heifers (testing animals) with BW with average of 249.3 kg and approximately 16 months old. These animals were weighed at the beginning and end of the experiment after 14 hours of solid and liquid fasting. Other 16 heifers (regulators animals) of the same genetic and contemporary compositions to the testing animals were added and removed from the experimental areas whenever there was a need to adjust the stocking rate on the pasture carrying capacity. The animal testing daily weight gain was used to estimate the performance of individual heifers. The weight gain per area (kg/ha) was calculated based on the average of individual weight gain of the testing animals and the total number of animals (testing and regulators) of each experimental area, animals day/ha. The components of the herbage mass (leaf blade, stem and senescent material) accumulation of forage and chemical composition of the forage were estimated by grazing cycle, from the sample of three paddocks of each experimental area. In each of these paddocks were collected three samples of forage, in the pre-grazing and post-grazing, to determine the mass of the components of forage. For the chemical composition, was collected a sample of forage per paddock in the pre-grazing. The financial analysis by treatment was carried out considering as revenue the amount of kilos produced and the selling price of kilos and as disbursements the expenditures on mineral supplement, concentrate, fertilizers, vermicides and labor. The variables related to the forage were analyzed statistically considering the structure of the compound symmetric covariance matrix using the SAS PROC MIXED. The variables related to the performance of the animals were analyzed using the GLM procedure of the same program. The averages were compared by Tukey test at 5% probability. It was observed individual gain of 0.562; 0.746 and 0.895 kg/day in animals were fed with 0; 0.50 and 1.0% of BW of concentrated supplement, respectively. Mean values of 653; 958 and 1438 kg/ha of weight gain and 5.44; 6.02 and 7.70 AU/ha of stocking rates were obtained with 0; 0.50 and 1.0% of concentrated supplementation of PC, respectively. There was no treatment effect on the leaf blade mass, stem mass, dead material mass and forage mass of the pre-grazing and post-grazing. However, these variables were influenced by grazing cycle. The grass heights in the pre-grazing were influenced by concentrated supplementation, with values of 37.2; 37.6 and 42.9 cm for the levels of supplementation of 0; 0.50 and 1.0% of BW, respectively. The forage chemical composition in the pre-grazing was not affected by concentrate supplementation strategies, with average mean values of 7.7; 8.9 and 8.3% crude protein and 64.1; 63.8 and 64.4% of NDF to levels of 0; 0.50 and 1% of concentrated supplementation of BW, respectively. The gross margin obtained was 1081.5; 1131.6 and 1242.2 R$/ha for levels of 0; 0.50 and 1.0% of BW, respectively. The concentrated supplementation of grazing beef heifers in the rainy season intensifies the individual weight gain by area and contributes to the production system profitability.